Efficiency and efficacy of planning and care on a post-anesthesia care unit: a retrospective cohort study - Bart van Tunen; Markus Klimek; Karin Leendertse-Verloop; Robert J. Stolker (BMC, 2020)
Abstract Background In the post-anesthesia care unit in our hospital, selected postoperative patients receive care from anesthesiologists and nursing staff if these patients require intensive hemodynamic monitoring or treatment to stabilize vital functions (e.g., vasopressor use and mechanical ventilation support) during a one-night admission. We investigated the agreement between elective preoperative planning for post-anesthesia care unit admission and the postoperative reality, along with the consequences of planning failures. Methods Data from records for 479 consecutive patients from June 1 to November 30, 2014, in a tertiary referral hospital were reviewed and analyzed. All patients admitted to PACU were included, along with patients scheduled to be referred to PACU but ultimately transferred to another ward. The primary outcome was the efficiency of planning PACU admission for elective patients. Secondary outcomes included secondary admissions to PACU or the intensive care unit (ICU) and 30-day morbidity and mortality. Results Of the 479 included patients, 342 (71%) were admitted per preoperative planning. Five patients (1%) needed cardiopulmonary resuscitation, and six (1%) did not survive the follow-up period. Patients admitted to PACU because of a shortage of beds in the ICU had the highest readmission (20%) and mortality rates (20%) (P = 0.01). Conclusions Preoperative planning for PACU admission was off-target for 29%. However, efficient care always takes precedence over efficient planning. In particular, downgrading patients to PACU because of a shortage of beds in the ICU was associated with a mortality increase.